Książka wyjścia - Tokarska-Bakir, Joanna (Poznańskie Studia Polonistyczne. Seria Literacka, 2015)
The text “The Book of Exit” delineates a perspective of animal studies understood as a consequence of the trauma theory and the Holocaust studies. At the foundations of the article are the views of Dominick LaCapry from 2004-2014, included by the author in the context of the current Polish and American cultural debates. In this interpretation the posthumanities and monster studies—vividly developing nowadays—are not only transformation but also overpower the melancholy of studies into trauma, completed at the price of parting from an individualistically crafted version of a liberal subject.